A importância da leitura literária: um estudo de caso na escola Basílio de Carvalho em Abaetetuba-PA - VILHENA, Marielen Ribeiro de (2019)
This work was developed from the analysis during the practice of supervised internship in the 7th grade class of the Basílio de Carvalho State School located in the urban area of the municipality of Abaetetuba, State of Pará, where I was able to observe the great difficulty of the students in practice of literary reading. From this fact it is proposed this work that aims to analyze how Portuguese-speaking teachers act with literature in their classes, having as a question: How do 7th grade teachers work with the teaching of literature in their classes? Thus, for the fundamentals of the work, it was necessary to use theoretical foundations, for this I used bibliographical research, as well as interviews and analyzes of the teaching practice for the considerations concerning this work. In this way, this experience allowed to analyze the positive and negative aspects, as well as the difficulties that surround the practice of literary reading in said institution.